Suicide and attempted suicide in bipolar disorder: a systematic review of risk factors. - Hawton, K; Sutton, L; Haw, C; Sinclair, J; Harriss, L (2005)
OBJECTIVE: To determine the main risk factors for suicide and nonfatal suicidal behavior in patients with bipolar disorder through a systematic review of the international literature. DATA SOURCES: Studies were identified through electronic searches of MEDLINE (1966-December 2003), EMBASE (1980-December 2003), PsycINFO (1872-November 2003), and Biological Abstracts (1985-December 2003) using index and free-text search terms for bipolar disorder, bipolar depression, manic depression, mania, and affective disorders; combined with terms for self-harm, self-injury, suicide, attempted suicide, automutilation, self-mutilation, self-poisoning, and self-cutting; and combined with terms for risk, case control, cohort, comparative, longitudinal, and follow-up studies. No language restrictions were applied to the search. STUDY SELECTION: Included studies were cohort, case-control, and cross-sectional investigations of patients with bipolar disorder in which suicide (13 studies) or attempted suicide (23 studies) was reported as an outcome. The selected studies also used diagnostic tools including the DSM, International Classification of Diseases, and Research Diagnostic Criteria. DATA SYNTHESIS: Meta-analysis of factors reported in more than 1 study identified the main risk factors for suicide as a previous suicide attempt and hopelessness. The main risk factors for nonfatal suicidal behavior included family history of suicide, early onset of bipolar disorder, extent of depressive symptoms, increasing severity of affective episodes, the presence of mixed affective states, rapid cycling, comorbid Axis I disorders, and abuse of alcohol or drugs. CONCLUSIONS: Prevention of suicidal behavior in patients with bipolar disorder should include attention to these risk factors in assessment and treatment, including when deciding whether to initiate treatment aimed specifically at reducing suicide risk.